Breeding, Plumages and Vocalisations of the Pied Bush Chat Saxicola caprata pyrrhonotus on Kisar Island, Lesser Sundas - Trainor, Colin R (KUKILA, 2012)
The Pied Bush Chat Saxicola caprata occurs widely in South, South-east Asia, and the Papuan region with 16 subspecies recognised including pyrrhonotus in the Timor region. Observations on the small island of Kisar, 25 km north of eastern Timor-Leste, revealed that the females differed from those of Timor, and may represent an undescribed subspecies. Females on Kisar had a cream-coloured throat with grey-brown streaks, and the breast and belly were streaked with dark brown, whereas those on Timor and Wetar have these parts plain light brown or rufous. The song of the Kisar bird also differed from those on Timor, but there is substantial variation in vocalisations among individuals, making quantitative inter-island comparisons difficult. Breeding was evident in October and the fledglings were found to be sexually-dimorphic as reported elsewhere for this species.